Functional expression of recombinant insulins in Saccharomyces cerevisiae - Mi-Jin Kim; Se-Lin Park; Hyun-Jin Kim; Bong Hyun Sung; Jung-Hoon Sohn; Jung-Hoon Bae (Microbial Cell Factories)
Abstract Background Since 1982, recombinant insulin has been used as a substitute for pancreatic insulin from animals. However, increasing demand in medical and food industries warrants the development of more efficient production methods. In this study, we aimed to develop a novel and efficient method for insulin production using a yeast secretion system. Methods Here, insulin C-peptide was replaced with a hydrophilic fusion partner (HL18) containing an affinity tag for the hypersecretion and easy purification of proinsulin. The HL18 fusion partner was then removed by in vitro processing with the Kex2 endoprotease (Kex2p), and authentic insulin was recovered via affinity chromatography. To improve the insulin functions, molecular chaperones of the host strain were reinforced via the constitutive expression of HAC1. Results The developed method was successfully applied for the expression of cow, pig, and chicken insulins in yeast. Moreover, biological activity of recombinant insulins was confirmed by growth stimulation of cell line. Conclusions Therefore, replacement of the C-peptide of insulin with the HL18 fusion partner and use of Kex2p for in vitro processing of proinsulin guarantees the economic production of animal insulins in yeast.